Effect of Molybdenum on Population of Bacillus Consortium and Production of Indole 3-Acetic Acid - Aliya Zahrah Adawiah; Sandra Amalia Riyadi; Reginawanti Hindersah; Pujawati Suryatmana (Agrologia, 2023)
Molybdenum (Mo) is one of nutrients that contributes on process of fixing N2 and it’s contained in growth medium of N2-fixing bacteria. Bacillus is bacterium that widely used as biofertilizer because it can fix N2 in the atmosphere and produce phytohormones in form of Indole 3-Acetic Acid (IAA) which are benefical for plant growth. The purpose of this research was to determine the effect of Mo addition on Bacillus consortium in a growth medium of 2%molasses + 10grams peptone + 3grams beef extract against vegetative cell population, spore population and IAA hormone production after incubated for 3, 6 and 9 days. This research was conducted at Soil Biology Laboratory, Faculty of Agriculture, Padjadjaran University. The method to calculate total population of vegetative cells is the serial dilution plate method with 80ºC heating for 30 minutes for total spore population, while the production of IAA hormone was measured using UV-Vis spectrophotometer with Salkowski reagent at a wavelength of 530 nm. All data subjected to Student-t test with p ≤ 0.05. The results of the study by using the Student-t test showed that Mo increased the vegetative cell population on day 3 but did not affect the vegetative cell population on day 6 and 9. The spore population of the Bacillus consortium was not determined by Mo. The production of IAA hormone in cultures with Mo was not different from that in cultures without Mo.